2018
DOI: 10.1530/rep-18-0041
|View full text |Cite
|
Sign up to set email alerts
|

ESTROGEN-REGULATED miRNA-27b IS ALTERED BY BISPHENOL A IN ENDOMETRIAL STROMAL CELLS

Abstract: MicroRNAs (miRs) are small molecules important for regulation of transcription and translation. The objective was to identify hormonally regulated miRs in human endometrial stromal cells and to determine the impact of the endocrine disruptor, bisphenol A (BPA), on those miRs. miR microarray analysis and multiple confirmatory cell preparations treated with 17β-estradiol (E2) and BPA altered miR-27b, let-7c, let-7e and miR-181b. Further, decidualization downregulated miR-27b. VEGFB and VEGFC were validated as ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 63 publications
(72 reference statements)
1
22
0
Order By: Relevance
“…The addition of ZEA and BPA also altered miRNA expression although these changes were not as remarkable as in the case of E2. Our results are in agreement with previous studies where BPA and ZEA altered miRNA expression in several other cell lines [ 20 , 60 , 61 , 62 , 63 ]. The observation that the effect of E2 on the expression of miR200s and miR203a was decreased by MPP, an ERα-selective antagonist, supports the presumption that ERα is involved in the regulation of these miRNAs.…”
Section: Discussionsupporting
confidence: 94%
“…The addition of ZEA and BPA also altered miRNA expression although these changes were not as remarkable as in the case of E2. Our results are in agreement with previous studies where BPA and ZEA altered miRNA expression in several other cell lines [ 20 , 60 , 61 , 62 , 63 ]. The observation that the effect of E2 on the expression of miR200s and miR203a was decreased by MPP, an ERα-selective antagonist, supports the presumption that ERα is involved in the regulation of these miRNAs.…”
Section: Discussionsupporting
confidence: 94%
“…Likewise, they revealed that BPA could decrease miR‐324. Moreover, the study of Reed et al showed a mechanism that BPA impairs miR‐27b levels thereby leading to changes in normal vasculogenesis and endometrial angiogenesis (Reed et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a bioinformatics analysis carried out using two different prediction algorithms (miRDB and TargetScan) allowed us to identify about 27 microRNAs that have Pparγ as their target gene. Among these, we searched those microRNAs whose expression can be affected by exposure to BPA [87][88][89][90][91]. Following this intersection, two candidate microRNAs, microRNA 27a and 27b, were selected from the above-mentioned list.…”
Section: Discussionmentioning
confidence: 99%